The Characteristic of YouTube Video as a Media of Anemia Education in Indonesia : Video YouTube sebagai Media Edukasi Anemia di Indonesia: A Narrative Review - Helmyati, Siti; Aryanti, Lintang; Basrowi, Ray Wagiu; Pratiwi, Dessy (Universitas Airlangga, 2023)
Background: The effectiveness of Anemia program in Indonesia must be supported by good public knowledge. YouTube can be used as a learning source to educate people about anemia. Anemia educational videos on YouTube have different characteristics that are interesting to analyze. Objectives: To identify the availability and describe the characteristics of anemia educational videos on YouTube. Methods: Videos were searched via google.com and youtube.com with the keywords